2014
DOI: 10.1089/rej.2013.1537
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Dahi Containing Lactobacillus acidophilus and Bifidobacterium bifidum Modulates the Formation of Aberrant Crypt Foci, Mucin-Depleted Foci, and Cell Proliferation on 1,2-Dimethylhydrazine-Induced Colorectal Carcinogenesis in Wistar Rats

Abstract: Aberrant crypt foci (ACF) and mucin-depleted foci (MDF) are pre-neoplastic lesions identified in the colon of carcinogen-treated rodents and in humans at high risk for colon cancer. The present study was carried out to divulge the protective potential of the probiotic Dahi containing Lactobacillus acidophilus LaVK2 and Bifidobacterium bifidum BbVK3 alone or in combination with piroxicam (PXC) on the development of early biomarkers of colorectal carcinogenesis in male Wistar rats administered 1,2-dimethylhydraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…Mohania et al. reported probiotic containing Lactobacillus acidophilus and Bifidobacterium bifidum displaying a downregulation effect on the Cytochrome P450 enzymes . Thus, the regulatory effect by PEP might be associated with the increased abundance of the probiotics as we described in the previous study .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Mohania et al. reported probiotic containing Lactobacillus acidophilus and Bifidobacterium bifidum displaying a downregulation effect on the Cytochrome P450 enzymes . Thus, the regulatory effect by PEP might be associated with the increased abundance of the probiotics as we described in the previous study .…”
Section: Discussionsupporting
confidence: 63%
“…Mohania et al reported probiotic containing Lactobacillus acidophilus and Bifidobacterium bifidum displaying a downregulation effect on the Cytochrome P450 enzymes. [35] Thus, the regulatory effect by PEP might be associated with the increased abundance of the probiotics as we described in the previous study. [22] Carbamoyl phosphate synthase 1 is involved in the urea cycle of ureotelic animals and plays an important role in removing excess ammonia, which relates to SCFAs oxidation in colonic epithelial cells.…”
Section: Proteins Associated With the Colonic Metabolismmentioning
confidence: 66%
“…Probiotic Dahi containing Lb acidophilus LaVK2 and B. bifidum BbVK3 alone or in combination with piroxicam modulated the development of early biomarkers of CRC in male DMH injected rats (Mohania et al, 2014).…”
Section: Improvement Of the Host's Immune Responsementioning
confidence: 92%
“…On the contrary, inflammatory biomarkers and side effects of chemotherapy were reduced in these patients (Golkhalkhali et al, 2018;Kotzampassi et al, 2015;Krebs, 2016;Z. Liu et al, 2015;Mego et al, 2015; reducing colitis, (l) increasing apoptosis, (m) increasing tumor suppressor miRNAs and, (n) increasing CXCR2 signaling (Agah et al, 2018;Arthur et al, 2013;Asha & Gayathri, 2012;Donohoe et al, 2014;Gamallat et al, 2016;Kahouli, Malhotra, Westfall, Alaoui-Jamali, & Prakash, 2017;Klewicka, Nowak, Zduńczyk, Cukrowska, & Błasiak, 2012;Kuugbee et al, 2016;Mendes et al, 2018;Mi et al, 2017;Mohania, Kansal, Kruzliak, & Kumari, 2014;Song et al, 2018;Talero et al, 2015;Walia, Kamal, Dhawan, & Kanwar, 2018;Zhang et al, 2015). studies include: intestinal microflora normalization, improvement of the gastrointestinal barrier, reduction of tumor formation, proliferation and growth of CRC cells and metastasis, reduction inflammatory responses, bacterial infection before and after colon cancer surgery.…”
Section: Human Studiesmentioning
confidence: 99%